Penanaman Nilai Karakter melalui Pembelajaran Ekstrakurikuler Drumband di SD N 2 Musuk Kecamatan Musuk Kabupaten Boyolali - Elsa Meylani; Udi Utomo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to explain how to instill character values ​​through extracurricular drumband activities at SD N 2 Musuk, located in Boyolali Regency. The rationale behind this research is because extracurricular activities are important in shaping students' character in accordance with the institution's vision and mission. The method applied in this study is descriptive qualitative. As research subjects, there are 45 students from grades 4, 5, and 6, and involving the principal, teachers, and coaches as sources of information. Data collection was conducted through observation, interviews, questionnaires, and documentation, which were then analyzed descriptively through data reduction, information presentation, and drawing conclusions. The research findings indicate that character instillation is carried out through a well-planned program and regular, scheduled practice. The character values ​​that were successfully instilled include discipline, responsibility, hard work, independence, collaboration, as well as religious attitudes and tolerance. The results of this activity are increased self-confidence and social skills of students, as well as the achievement of non-academic achievements that are a source of pride for the school.